2016
DOI: 10.1039/c6ob01227b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of Ni-NTA-modified β-annulus peptides into artificial viral capsids and encapsulation of His-tagged proteins

Abstract: β-Annulus peptides bearing Cys at the N-terminal from tomato bushy stunt virus were synthesised using a standard Fmoc-protected solid-phase method, and the peptide was modified with Ni-NTA at the N-terminal. The Ni-NTA-modified β-annulus peptide self-assembled into virus-like nanocapsules of approximately 40 nm in diameter. The critical aggregation concentration of these nanocapsules in 10 mM Tris-HCl buffer (pH 7.3) at 25 °C was 0.053 μM, which is 470 times lower than that of unmodified β-annulus peptides. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…These self-assembled peptide gels could have then also stabilized or localized primitive cells through their adhesive properties [ 134 ] or even directly affected local geology by driving the formation of hydroxyapatite (Ca 5 (PO 4 ) 3 (OH)) [ 135 ] (similar to what has been seen in peptide amphiphile nanofibers) or other minerals. There are many other examples of self-assembled peptide structures independent of mineral surfaces composed of short, prebiotically available peptides with emergent properties important for the initial emergence of life including binding [ 136 ], segregation [ 137 , 138 ], encapsulation [ 139 ], or even catalysis [ 140 , 141 ]; these structures are worth further study in the context of co-assembly with mineral surfaces to determine whether additional unique structures or functions could have emerged.…”
Section: Case Studiesmentioning
confidence: 99%
“…These self-assembled peptide gels could have then also stabilized or localized primitive cells through their adhesive properties [ 134 ] or even directly affected local geology by driving the formation of hydroxyapatite (Ca 5 (PO 4 ) 3 (OH)) [ 135 ] (similar to what has been seen in peptide amphiphile nanofibers) or other minerals. There are many other examples of self-assembled peptide structures independent of mineral surfaces composed of short, prebiotically available peptides with emergent properties important for the initial emergence of life including binding [ 136 ], segregation [ 137 , 138 ], encapsulation [ 139 ], or even catalysis [ 140 , 141 ]; these structures are worth further study in the context of co-assembly with mineral surfaces to determine whether additional unique structures or functions could have emerged.…”
Section: Case Studiesmentioning
confidence: 99%
“…The hollow internal space of the β‐annulus capsid has been utilized to encapsulate various guest molecules by simple electrostatic interaction or conjugation with guest‐binding peptides to the β‐annulus peptide . Since the cationic N‐terminal region of the β‐annulus peptide is directed to the interior surface, the anionic dyes were efficiently encapsulated in the capsid, in contrast to cationic dyes .…”
Section: Self‐assembled Artificial Viral Capsidsmentioning
confidence: 99%
“…By a similar strategy, His‐tag GFP was encapsulated in the capsid by the insertion of Ni‐NTA (nitrilotriacetic acid) into the N‐terminus of the β‐annulus peptide (Figure d, upper) . The Ni‐NTA‐modified β‐annulus peptide retained the self‐assembly capability to form the capsid with 46.8±10.5 nm diameter (Figure d, bottom).…”
Section: Self‐assembled Artificial Viral Capsidsmentioning
confidence: 99%
“…It is also suggested that the C-terminals of the peptides are directed to the surface of the nanocapsules, while the N-terminals are directed toward the interior [21]. These properties made it possible to encapsulate anionic dyes, DNA [21], His-tagged proteins [22], and anionic CdTe quantum dots [23] into the artificial viral capsids. We also constructed artificial viral capsids decorated with gold nanoparticles by C-terminal modification of the β-annulus peptides [24].…”
Section: Introductionmentioning
confidence: 99%